An empirical investigation on Cu/Ethylene Glycol nanofluid through a concentric annular tube and proposing a correlation for predicting Nusselt number - A. Jafarimoghaddam; S. Aberoumand (Alexandria Engineering Journal, 2016)
The investigation indicates an experimental study on the convective heat transfer of Cu/Ethylene Glycol nanofluid flow inside a concentric annular tube with constant heat flux boundary condition and proposes a novel correlation for the prediction of Nusselt number. For extending the previous study by Jafarimoghaddam et al., we selected the nanoparticles with the average size of 20 nm and also other conditions of the experiment are based on Jafarimoghaddam et al. (2016) [1]. The applied nanofluid was prepared by Electrical Explosion of Wire technique with no accumulation during the experiment. The tube was heated using an electrical heating coil covered it. The effects of different parameters such as flow Reynolds number and nanofluid particle concentration on heat transfer coefficient are studied. The acquired experimental data were used to establish a correlation for predicting Nusselt number of nanofluid flow inside the annular tube. This correlation has been presented by using the exponential regression analysis and least square method. Correlation is valid for Cu/Base Ethylene Glycol nanofluid flow with the volume concentrations between 0.011 and 0.171 in the hydrodynamically fully developed laminar flow regime with Re < 160 which is most applicable in micro heat sinks.